Analisis Praktik Koordinasi Manfaat (Coordination of Benefit) Layanan Rawat Inap di Indonesia - Dewi, Fera Mutiara; Hidayat, Budi (UI Scholars Hub, 2017)
Nowadays, some people may have double insurance. Besides having compulsory insurance that regulated by government, they also have additional health insurance which is not mandatory. This condition has opened up opportunities for Coordination of Benefit (COB) in Indonesia, especially in JKN era. Unfortunately, in practice COB still not executed according to the principle of general rules of insurance. This research seeks to analyze the practice of the COB and COB fee scale in Indonesia. The method used is the observational study with cross sectional design. The modeling uses an econometric approach that is a two-part model which separates the process between the COB practice and the COB funds. The result of the research states that age covariate, LOS, and circulatory system diseases show significant effects in statistical testing. Lack of coordination between providers and assurer or between assurer and assurer, causes increasing potential moral hazard by both participants and providers so that participants may get double coverage. The suggestions of this research are first the need to create an independent organization that manages COB and second the need to made regulation of COB.